Analysis and calculation method for multiple faults in low-resistance grounded systems with inverter-interfaced distributed generators based on a PQ control strategy. (June 2022) - Li, Jie; Bi, Haoran; Li, Chengxin; Li, Jing; Zeng, Dehui; Wang, Gang
Highlights: A PQ control strategy and fault equivalent model of the IIDG. An analysis and calculation model for multiple faults with IIDGs. A novel systematic fault analysis and calculation method with IIDGs. An iterative correction algorithm. Abstract: The short-circuit characteristics of low-resistance grounded systems (LRGSs) under multiple faults have fundamentally changed because of the high penetration level of inverter-interfaced distributed generators (IIDGs). However, an analysis and calculation method for multiple faults (ACMMF) with IIDGs that is a standard basis for fault features, relay protection, safe evaluation and design of LRGSs is currently lacking. A novel systematic ACMMF is analytically proposed in this paper based on ideal transformer and multiport network theory. Based on the proposed ACMMF, composite networks under various fault conditions are established, which provides a straightforward presentation of fault current paths and equivalent impedance and simplifies the modelling procedure for fault analysis and calculation. Furthermore, to overcome the strong nonlinear inter-IIDG couplings, an iterative correction algorithm is proposed for accurate IIDG fault current calculations. Finally, the accuracy of the proposed method is verified by PSCAD/EMTDC simulation. The results show that the proposed methods have good adaptivity to different system structures, operation modes, fault types and flexible access of IIDGs.